Single Incision Laparoscopic Cholecystectomy (SILC) using a novel glove port technique: Early unit experience - Othman H.; Ikhwan S.M.; Azman A.; Zuhdi Z.; Ariffin AC; Jarmin R. (Ministry of Health, 2024)
Indexed by SCOPUS